The Impact of Lesson Study on Primary School Teachers’ Knowledge and Skills in Differentiating Primary School Mathematics Instruction: A Digital Mixed Methods Approach - Harsono, Mariana (Curtin University, 2016)
This digital mixed methods study was conducted in two Indonesian primary schools to investigate the impact of Lesson Study on teachers’ knowledge and skills in differentiating mathematics instruction to meet the various abilities of the students. The lessons were videoed and analysed using Multimodal Analysis Video software to study the relations between Mathematical Pedagogical Content Knowledge and the teachers’ actions in differentiating mathematics instruction. The findings suggest that Lesson Study can be a vehicle for enhancing teachers’ knowledge to differentiate the instruction.